Chronic Suppurative Otitis Media leading to cerebellar brain abscess, still a problem in 21st century: A case report. (August 2022) - Ahmad, Rana Uzair; Ashraf, Muhammad Fawad; Qureshi, Muhammad Ahmad; Shehryar, Muhammad; Tareen, Haseeb Khan; Ashraf, Muhammad Aizaz
Abstract: Introduction and importance: Chronic suppurative otitis media (CSOM) is a chronic inflammation of the middle ear associated with tympanic membrane rupture and purulent discharge for at least 6 weeks. Owing to the proper use and easy availability of antibiotics, these types of cases are rare in developed regions, but they are still occasionally seen in the developing world with poor hygiene and a lack of availability of antibiotics and immunizations. Case presentation: Patient presented with complaints of headache, yellow-colored discharge from ear, fever and vomiting. The patient's Glasgow Coma Scale (GCS) was 12/15, neck stiffness and positive Kernig's sign, horizontal nystagmus and exaggerated deep tendon reflexes. Positive CSF findings and Magnetic Resonance Imaging showing right sided cerebellar abscesses, led to the diagnosis of right-sided CSOM leading to cerebellar brain abscess. Patient was treated with anti-pyrectics, intravenous mannitol, IV and topical antibiotics and IV-dexamethasone. Abscess evacuation was performed in neurosurgery department while mastoidectomy was performed in ENT department. Patient's condition improved quickly and was discharged with regular follow-up. Discussion: CSOM is a long-standing middle ear infection, associated with ear discharge and permanent perforation of the tympanic membrane. Divided into two main types, a) Tubo tympanic b) Atticoantral. CSOM occasionally presents with severe intracranial complications, especially in developing countries. Conclusion: CSOM is a chronic inflammation of the middle ear. Without early and effective management, it can lead to serious intracranial complications. So, diagnosis of complications like cerebellar abscess should be on the differential while dealing with patients with CSOM in developing countries. Highlights: CSOM is a chronic inflammation of the middle ear associated with tympanic membrane rupture and purulent discharge for at least 6 weeks. Commonly seen complications include infections leading to auricular sinus, subperiosteal abscess and meningitis. This case report deals with discussion of a patient who presented with symptoms of meningoencephalitis and cerebellar brain abscess.